Efeito dos serviços de polinização na produção e qualidade de sementes de girassol (Helianthus annuus L.) - Melo, Ana Luisa de Sousa e Castro (2014)
Bees are responsible for the maintenance of native and cultivated plant species because they present high fidelity, floral constancy and specialized resources collection behavior during their visits with great importance for the maintenance of pollination services. Among cultivated plants, 75% are directly or indirectly dependent of pollinators. Apis melifera, is the main species used for crop pollination, however due to its recent decline, native bees (Non-Apis) has been considered as a viable alternative for pollination services. Among commercial crops, we highlight the sunflower, a oilseed with major global economic importance which benefits from bee pollination. Apis mellifera is the main pollinator of this crop, however the presence of Non-Apis bees increment production by increasing the number of visits of A. mellifera. Considering the typical use and the importance of A. mellifera for sunflower pollination and the difficulties caused by pollinators decline, the main objectives were (i) to identify floral visitors in an experimental sunflower crop and evaluate the influence of these visitors in pollination, production and quality of seeds and (ii) to determine the effect of different functional pollinators groups (Apis and non-Apis) in the quantity (weight) and quality (amount of oil) of seeds. The study was conducted in the Fazenda Água Limpa (UFU), Uberlândia, MG between the months of June and July of 2012 in an experimental sunflower crop (Helianthus annuus L.). To assess the importance of pollination by bees on production and quality of sunflower seeds, we held an experiment to exclude floral visitors. 30 sunflower inflorescence were bagged for negative control (excluding visitors) and another 30 for open pollination. After the maturation period, the inflorescence were collected for oil production quantification. Floral visitors survey was carried out through a census along crop lines There was a significant difference between pollination negative control and open pollination treatments for the parameters thousand achenes weight and oil quantity in 5 grams of seed. There was a increase of 49% in seed weight and 305% in the amount of oil produced. 252 native bees corresponding to 28 genera and 14 species and 7 tribes were collected. The tribe Apini presented the highest number of species and a greater number of individuals. There was a positive correlation between seed weight and the number of visits of Non-Apis. Thus, the consortium management of A. mellifera and Non-Apis bees combined with the conservation of natural vegetation surrounding crop areas will result in a greater increase in productivity and quality of sunflower seeds.